1994
DOI: 10.1177/027112149401400206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Cocaine Exposure on Mother--Infant Interaction and Infant Arousal in the Newborn Period

Abstract: This study compared the interactive behavior of cocaine-using mothers and their neonates with a control group of drug-free mothers and their newborns. Infant arousal levels and infant-maternal interaction behaviors were measured during play and attention-getting tasks. The effects of three different social stimulation conditions, provided by the mothers to maintain infant states more conducive to interaction, were also investigated. The cocaine-exposed infants were asleep or distressed for significantly longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 31 publications
(21 reference statements)
5
50
0
Order By: Relevance
“…Although group differences in other prenatal substance use and various characteristics of the child and caregiving environment did not account for the findings in this study, there may have been differences in the caregiver-child relationships that contributed to these findings. Certainly, previous studies have found that mother-infant/child dyadic interactions have been more impaired in women who use cocaine during pregnancy with cocaine abusing women being more insensitive or less responsive in the care of their infants (Eiden et al, 2002Gottwald & Thurrman, 1994;Minnes et al, 2005). Caregiver mediation of arousal and direct instruction in self-regulation are important elements in the development of age-appropriate behavioral regulation skills (Ruff & Rothbart, 1996) and these instructions and learning experiences may mediate the interactive elements of the different arousal systems (Posner & Rothbart, 2006), resulting in alterations of physiological and behavioral responses to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Although group differences in other prenatal substance use and various characteristics of the child and caregiving environment did not account for the findings in this study, there may have been differences in the caregiver-child relationships that contributed to these findings. Certainly, previous studies have found that mother-infant/child dyadic interactions have been more impaired in women who use cocaine during pregnancy with cocaine abusing women being more insensitive or less responsive in the care of their infants (Eiden et al, 2002Gottwald & Thurrman, 1994;Minnes et al, 2005). Caregiver mediation of arousal and direct instruction in self-regulation are important elements in the development of age-appropriate behavioral regulation skills (Ruff & Rothbart, 1996) and these instructions and learning experiences may mediate the interactive elements of the different arousal systems (Posner & Rothbart, 2006), resulting in alterations of physiological and behavioral responses to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cocaine using mothers have been reported to display higher negative affect during interactions with their infants (Burns, Chetnik, Burns, & Clark, 1991a;Eiden, 2001;LaGasse et al, 2003), and be more disengaged and passive during mother-infant interactions (Gottwald & Thurman, 1994;Molitor, Mayes, & Ward, 2003). Maternal parenting behavior plays a critical role in helping children manage their arousal and keep distress within tolerable limits in infancy.…”
Section: Indirect Effects and Moderationmentioning
confidence: 99%
“…The few studies focusing on this crucial influence on development have reported mixed results. On one hand are studies reporting that cocaine-using mothers are more likely to be disengaged from their newborns (Gottwald & Thurman, 1994) and exhibit lower responsivity and reciprocity (Burns, Chethik, Burns, & Clark, 1991). Along similar lines, a recent study of face-to-face interactions among polydrug cocaine-using mothers and their infants at 3 and 6 months of age indicated that these mothers were less attentive and engaged in fewer dyadic interactions than noncocaine or nondrug-using mothers (Mayes, Feldman, Granger, Haynes, Bornstein, & Schottenfeld, 1997).…”
mentioning
confidence: 99%